Lignin-carbohydrate complexes from sugarcane bagasse: preparation, purification, and characterization - Singh, R.; Singh, S.; Trimukhe, K. D.; Pandare, K. V.; Bastawade, Kulbhushan B.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2005)
Lignin-carbohydrate complexes were isolated from sugarcane bagasse by a process, which yielded sulfur-free lignins. These could be made carbohydrate-free, if necessary, by treatment with xylanase enzyme. A study of the preparation, purification, and characterization of such lignin-carbohydrate complexes, comparison with commercial lignin samples (wood based as well as bagasse based) and some other lignin derivatives was made by using a variety of analytical tools such as FTIR, HPLC at three different UV-wavelengths, GPC, thermal analysis and elemental analysis. The use of such a diverse range of lignin-carbohydrate complex samples enabled us to predict the sensitivity of the various analytical techniques for characterization of complex polymers containing carbohydrate moieties. Evidence for lignin-carbohydrate complex was detectable by FTIR as well as HPLC studies. Thermal analysis studies showed the crucial effect of carbohydrate groups, the content of aliphatic chains, and the sulfur content of the lignins. Generalized structures of lignin-carbohydrate complexes obtained from various sources using different preparation methods and chemical modifications are presented. This will aid the applications development effort with advantageously using lignins containing low levels of carbohydrate moieties as reactive sites as well as biodegradability inducing sites. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: biodegradability; hardwood lignins; lignin-carbohydrate complex; softwood lignins; Sugarcane bagasse; sulfur-free lignins; xylanase enzyme

Metal complexes of crosslinked chitosans. part II. an investigation of their hydrolysis to chitooligosaccharides using chitosanase - Trimukhe, K. D.; Bachate, S.; Gokhale, D. V.; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2007)
This paper investigates the behavior of crosslinked chitosans and metal-complexed crosslinked chitosans under similar hydrolytic conditions. Crosslinked chitosans with trimellitic anhydride, diisocyanatohexane, and dibromodecane as crosslinking agents under heterogenous reaction conditions were used as metal complexing agents by equilibrating them with metal salts such as ZnCl2, MnSO4, CuSO4, CdSO4, Pb(NO3)(2), and HgCl2. Crosslinked chitosan without metal complexation had the same hydrolytic behavior as uncrosslinked chitosan. However, when the crosslinked chitosans were complexed with metals, their rates of hydrolysis and extent of hydrolysis were significantly reduced. Thus, while for chitosan about 840 mu g/ml reducing sugar was produced in 4 h time, and 780 mu g/ml was produced for diisocyanatohexane crosslinked chitosan, only 400 mu g/ml and 320 [mu g/ml reducing sugars were produced for cadmium sulfate with crosslinked chitosan and diisocyanatohexane crosslinked chitosan, respectively. Similar results are obtained for other crosslinking agents. Studies on preincubation of the metal with the enzyme show that of the metals studied, Mn has no effect on preincubatioin with the enzyme, Hg, Cd, Pb, and Cu completely deactivates the enzyme, while Zn reduces the enzyme activity by about 43.3%. Preincubation of the metal salts with the chitosan shows that Hg and Cu completely deactivate the molecule from enzyme hydrolysis, Cd and Zn inactivate it to the extent of 56.8% and 43.3%, respectively, while Mn has no effect. Availability of the amino functions seems to be a key feature for the chitosanase to hydrolyze the chitosan polymer. This was also proved by the significant increase in the extent of hydrolysis for chitosan samples with 88% (final value 1120 mu g/ml reducing sugar) and 85% deacetylation (final value 840 mu g/ml reducing sugar). HPIC studies of the products show that a variety of oligomers are produced in the chitosanase enzyme hydrolytic reaction. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: chitooligosaccharides; Chitosan; chitosanase hydrolysis; Crosslinked chitosan; metal-complexed crosslinked chitosan

Complexation of heavy metals by crosslinked chitin and its deacetylated derivatives - Trimukhe, K. D.; Varma, Anjanikumar (Carbohydrate Polymers, 2008)
Chitin was crosslinked using diisocyanatohexane (HDI), trimellitic anhydride (TMA), and dibromodecane (DBD), then deacetylated in strong aqueous alkali. This led to a product with amine functional groups on the exposed surface of the crosslinked chitin, which could be utilized for complexation with heavy metals. Thus, a key feature of the crosslinked derivatives prepared was that only the hydroxy Groups were utilized in the crosslinking reaction, and the acetylamino groups of chitin were hydrolyzed only after the crosslinking was accomplished. This ensured that all amino groups of the chitosans so produced would be available for metal complexation, and not partially used up in crosslinking. This proposed advantage was proved by the similar binding observed for heavy metals like Hg (348-372 mg/g), Cu (91-119 mg/g), Zn (71-92 mg/g), Mn (3-10 mg/g), Cd (121-160 mg/g), and Pb (32-86 mg/g) using these crosslinked polymers, whereas the control polymer (uncrosslinked chitosan powder) had complexation values for Hg (348-361 mg/g), Cu (100-106 mg/g), Zn (81-92 mg/g), Mn (4-7 mg/g), Cd (135 mg/g), and Pb (25-59 mg/g). Additionally, in a case where chitosan was crosslinked with HDI. the amino groups were consumed in the crosslinking reaction, and the metal complexation capacity has found to be decreased for Cu (91-109 mg/g), Cd (133 mg/g), and Zn (71-77 mg/g), while remaining nearly the same for Hg (362 mg/g). The literature value for Cu complexation is 59.67 mg/g for chitosan crosslinked with glutaraldehyde. The crosslinked derivatives have the added advantage of insolubility even in low pH aqueous media, making their repeated re-use possible. Further, these crosslinked derivatives could be used in powder form, and the additional step of preparing beads was found to be not necessary for ease of separation of the crosslinked powder by filtration. The binding capacity of various crosslinked chitin and deacetylated derivatives for Cu, Cd, Hg, Zn, Mn. and Pb was in the region of 100, 140, 360 88, 5, and 60 mg/g (rounded off values) of polymer, respectively, very close to the values obtained for uncrosslinked chitosan. The metal binding for crosslinked chitosan was slightly lower than that of crosslinked chitin and deacetylated derivatives, due to use of some amino groups in crosslinking. For Cu ions, the Langmuir equation was found to be the best fit for HDI crosslinked deacetylated chitin and TMA crosslinked deacetylated chitin. The morphological studies conducted using WAXRD are in close agreement with the metal complexation data, showing complete loss of original chitosan peaks for the heavily complexed derivatives, and minor changes for the weakly complexed metals. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Chitosan; Crosslinked chitosan; deacetylated chitin; metal complexation; Morphology

Environment friendly crosslinked chitosan as a matrix for selective adsorption and purification of lipase of aspergillus niger - Trimukhe, K. D.; Mahadik, N. D.; Gokhale, D. V.; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2008)
Chitosan and its derivatives have been used as affinity matrices for purification of lipase from Aspergillus niger NCIM 1207. Trimellitic anhydride (TMA)-crosslinked deacetylated chitin adsorbed lipase selectively, yielding approximately 5-fold purification of the crude lipase with 70% yield. Further 9-fold purification occurred on eluting through Sephacryl-100. These results suggest that chitosan derivatives can be used as inexpensive biopolymer matrices for the purification of lipases for industrial applications. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Chitosan; Lipase; Matrix; Purification

Morphological study of heavy metal complexes of chitosan and crosslinked chitosans by SEM and WAXRD - Trimukhe, K. D.; Varma, Anjanikumar (Carbohydrate Polymers, 2008)
Metal complexes of salts of Hg, Cu, Cd, Pb, Zn, and Mn with chitosan and crosslinked chitosans were prepared, and their morphologies were studied using scanning electron microscopy and wide angle X-ray diffraction. The metal ions which were specifically and strongly complexed to the amino functions of chitosans, like Hg, showed smooth surface morphology inspite of large number of ions complexed (372 mg/g of chitosan). The presence of metal ions on the surface of the chitosans could be detected with decrease in metal ion binding, in the following sequence Hg > Cu > Cd > Zn > Pb > Mn. Particularly in the case of Pb ions, the presence of these ions is clearly seen on the surface of the polymer by SEM. The number of ions of Mn complexed on the polymers was too few (5 mg/g of chitosan) to be visible. SEM of Hg and Cu complexes do not show the ``holes'' observed in the crosslinked polymers as they bind specifically to amino groups of chitosan, but for Cd, Zn, Mn, and Pb complexes, these ``holes'' are clearly visible. These results are also in agreement with the morphologies studied by WAXRD. The metal complexation data for each of these metal ions was also in the same sequence. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Chitosan; Crosslinked chitosan; metal complex; Morphology; SEM; WAXRD

Metal complexes of crosslinked chitosans: correlations between metal ion complexation values and thermal properties - Trimukhe, K. D.; Varma, Anjanikumar (Carbohydrate Polymers, 2009)
A series of heavy metal complexes of crosslinked chitosans were evaluated by thermogravimetric studies. The metal complexes with Cu, Cd and Hg ions exhibiting the highest complexing ability to chitosans (Hg 354-364, Cu 100-112, and Cd 121-160, in mg/g chitosan), had the lowest onset of degradation temperatures (range 194-210 degrees C) and the lowest final degradation temperatures (generally less than 294-304 degrees C for Hg, 296-338 degrees C for Cu, and 305-368 degrees C for Cd complexes). Mn ion, with the lowest binding to chitosans (Mn 5-7 mg/g), showed the reverse behavior, having onset (240-248 degrees C) and final degradation temperatures (range 300-368 degrees C). Zn (binding 74-87 mg/g) and Pb (binding 39-62 mg/g) ions have a binding ability intermediate to Cu/Cd/Hg and Mn extremes, and therefore the effects on onset and final degradation temperatures are intermediate to these values. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chitosan; Crosslinked chitosan; Degradation temperature; Metal complexes; Thermal properties; Thermogravimetry

Effect of mixed acid catalysis on pretreatment and enzymatic digestibility of sugar cane bagasse - Pal, Siddhartha; Joy, Shereena; Kumbhar, Pramod; Trimukhe, K. D.; Varma, Anjanikumar; Padmanabhan, Sasisanker (Energy & Fuels, 2016)
Aqueous pretreatment using homogeneous acid catalyst is considered as a low-cost technology in the production of lignocellulosic bioethanol. To establish the synergism of mixed acids, pilot-level aqueous pretreatments of bagasse covering a wide range of combined severity (CS) were carried out. To investigate the effect of application of mixture of acids on xylose hydrolysis as well as glucose hydrolysis via pretreatment and enzymatic hydrolysis, the following three combinations of acids were explored: (1) oxalic acid + sulfuric acid (organic + mineral acid), (2) phosphoric + sulfuric acid (mineral acids), and (3) ferric chloride + sulfuric acid (Lewis acid with a mineral acid). Of the pretreatments evaluated, the synergism was most pronounced for the combination of sulfuric and phosphoric acid, which resulted in more than 90% conversion of hemicellulose to xylose and 70% conversion of cellulose to glucose through enzymatic hydrolysis. Fourier transform infrared (FTIR) studies of pretreated samples showed higher syringyl/guaiacyl (S/G) ratio for sulfuric and phosphoric acid combination pretreatment, leading to higher enzymatic conversion. FTIR and dynamic light scattering (DLS) experiments conducted on pretreated sugar cane bagasse provided useful correlation with regard to the pretreatment type, particle size, and enzymatic hydrolysis.